2000
DOI: 10.1159/000063441
|View full text |Cite
|
Sign up to set email alerts
|

Critical Ages and Stages of Puberty in the Accumulation of Spinal and Femoral Bone Mass: The Validity of Bone Mass Measurements

Abstract: In growing children, lumbar and femoral areal bone mineral density (aBMD), as measured by dual-energy X-ray absorptiometry (DXA), is influenced by skeletal growth and bone size. Correction of lumbar bone mineral density (BMD) for bone volume (volumetric BMD [vBMD]), by the use of mathematical extrapolations, reduces the confounding effect of bone size, but vBMD remains dependent on age and bone size during growth. Femoral (neck and mid-shaft) vBMD, assessed by DXA, is independent of age prior to puberty, but a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(2 citation statements)
references
References 27 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…Whilst growth and virilisation are the most visible observations of puberty, the period of puberty is further defined by other significant physical, emotional and psychological changes that are primarily due to the increase in systemic sex steroid concentrations. Physically, puberty is a critical period during which humans achieve optimal bone mass [13] and there is accumulating evidence that in adults with childhood-onset chronic disease, abnormalities of bone health seem to develop during the peri-pubertal years [14,15] and may be related to hypogonadism [16]. Late sexual maturation in boys may also have an impact on psychological well-being and has been shown to be associated with altered behaviour and poorer educational attainment [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Whilst growth and virilisation are the most visible observations of puberty, the period of puberty is further defined by other significant physical, emotional and psychological changes that are primarily due to the increase in systemic sex steroid concentrations. Physically, puberty is a critical period during which humans achieve optimal bone mass [13] and there is accumulating evidence that in adults with childhood-onset chronic disease, abnormalities of bone health seem to develop during the peri-pubertal years [14,15] and may be related to hypogonadism [16]. Late sexual maturation in boys may also have an impact on psychological well-being and has been shown to be associated with altered behaviour and poorer educational attainment [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…When corrected the difference in BMD is statistically significant in age groups 16 through 18 years (5). Correction of lumbar BMD for bone volume by the use of mathematical formulations reduces the effect of bone size but vBMD remains dependent on age and bone size during growth except that femoral neck vBMD is independent of age prior to puberty (5,(18)(19)(20)(21)(22). In 345 Turkish healthy children (2-28 yr) it has been shown that volumetric BMD reduces the effects of age on BMD but it is still dependent on age (unpublished data, Go¨ks¸en et al, Ege University Faculty of Medicine, Izmir).…”
Section: Discussionmentioning
confidence: 99%